(untitled) (Faridpur Medical College Journal, 2011)
Diabetes mellitus is a heterogeneous group of syndromes characterized by an elevation of blood glucose caused by a relative or absolute deficiency of insulin. The incidence of diabetes is growing rapidly worldwide. Drug treatment for diabetes mellitus is expensive and carries risks for many adverse effects. Bangladesh is a rich emporium of medicinal plants useful in the treatment of diabetes. The study was performed to investigate the blood glucose lowering effect of Swietenia mahagoni seeds in experimentally induced diabetic rats. Twenty four healthy Long Evans Norwegian strain of rats were included in the study and divided into four groups (A, B, C and D) comprising 6 rats each. Diabetes was induced by alloxan (120 mg/kg body weight). Administration of ethanolic extract of Swietenia mahagoni seeds (group-B) produced no significant change in the blood glucose level as compared to control (group-A). Administration of ethanolic extract of Swietenia mahagoni seeds in group-D produced a significant reduction in blood glucose level as compared to diabetic control (group-C). Histological examination of pancreas showed destruction of beta cells in Islets of pancreas in group-C whereas retaining of islets and few degranulations of beta cells of pancreas found in group-D. These observations and results provide information that ethanolic extract of Swietenia mahagoni seeds has hypoglycaemic effect in experimentally induced diabetic rats which requires further investigation. Key words: Diabetes mellitus; Swietenia mahagoni; Alloxan; Rat; Blood glucose. DOI: http://dx.doi.org/10.3329/fmcj.v6i2.9203 FMCJ 2011; 6(2): 70-73